2008
DOI: 10.1785/0120070124
|View full text |Cite
|
Sign up to set email alerts
|

Induced Dynamic Nonlinear Ground Response at Garner Valley, California

Abstract: We present results from a prototype experiment in which we actively induce, observe, and quantify in situ nonlinear sediment response in the near surface. This experiment was part of a suite of experiments conducted during August 2004 in Garner Valley, California, using a large mobile shaker truck from the Network for Earthquake Engineering Simulation (NEES) facility. We deployed a dense accelerometer array within meters of the mobile shaker truck to replicate a controlled, laboratory-style soil dynamics exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
(20 reference statements)
2
10
0
Order By: Relevance
“…The in situ nonlinearity across the differential strain range of ∼6 × 10 −8 is consistent with the response induced by similar strains in the laboratory [ TenCate et al , ; Pasqualini et al , ]. Thus, our results extend the compatibility between field and laboratory observations at large strain amplitudes [ Lawrence et al , ; Renaud et al , ] toward a smaller deformation regime.…”
Section: Discussionsupporting
confidence: 89%
“…The in situ nonlinearity across the differential strain range of ∼6 × 10 −8 is consistent with the response induced by similar strains in the laboratory [ TenCate et al , ; Pasqualini et al , ]. Thus, our results extend the compatibility between field and laboratory observations at large strain amplitudes [ Lawrence et al , ; Renaud et al , ] toward a smaller deformation regime.…”
Section: Discussionsupporting
confidence: 89%
“…Their model suggests that triggering may be caused by a shear modulus reduction (softening) due to the passage of seismic waves and is based on laboratory experiments [63][64][65]. In situ field experiments with induced ground motions have also demonstrated that seismic waves can cause material softening [66][67][68]. These laboratory and field experiments suggest that triggering may not be due to the very small increase in the shear stress by the propagating elastic waves, but rather may be due to the reduction in the shear modulus of the fault gouge material, leading to failure.…”
Section: A Effectiveness Of Boundary Vibration In Dynamic Triggeringmentioning
confidence: 99%
“…Stokoe and Darendeli (1998) performed laboratory tests to extract the G-γ curve of the surficial sediments; these results will be used as a reference for our analysis. Moreover, Lawrence et al (2008) studied the nonlinear response of GVDA using induced vibration with acceleration of more than 1g. By inverting the dispersion curves, they observed the greatest change in S-wave velocity nearest the surface (up to a depth of 4 m) related to the nonlinear response of the uppermost layers.…”
Section: Introductionmentioning
confidence: 99%